2015
DOI: 10.9738/intsurg-d-14-00006.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glissonean Pedicle Approach for Centrally Located Hepatocellular Carcinoma in Mongolia

Abstract: Approaches to surgical resection of centrally located HCC remain controversial. Traditionally, hemi- or extended hepatectomy is suggested. However, it carries a high risk of postoperative complications in patients with cirrhosis. An alternative approach is Glissonean pedicle transection method. This study was conducted to assess the surgical and survival outcomes associated with central liver resection using the Glissonean pedicle transection. Sixty-nine patients with centrally located HCC were studied retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…16 Mongolia et al reported that the Glissonian pedicle approach had comparable surgical and long-term survival outcomes versus conventional liver resection. 27 Similarly, in a prospective randomized trial, Figueras et al compared hilar dissection versus the Glissonian approach among patients undergoing a major hepatectomy. 15 Although en bloc transection of the Glisson's pedicle was faster than isolated ligation of each element in the hilar pedicle, the duration of pedicle clamping was shorter with hilar dissection, probably due to an initial period of Pringle maneuver applied for introduction of the stapler with the Glissonian approach.…”
Section: Glissonian Versus Traditional Hilar Approachmentioning
confidence: 99%
“…16 Mongolia et al reported that the Glissonian pedicle approach had comparable surgical and long-term survival outcomes versus conventional liver resection. 27 Similarly, in a prospective randomized trial, Figueras et al compared hilar dissection versus the Glissonian approach among patients undergoing a major hepatectomy. 15 Although en bloc transection of the Glisson's pedicle was faster than isolated ligation of each element in the hilar pedicle, the duration of pedicle clamping was shorter with hilar dissection, probably due to an initial period of Pringle maneuver applied for introduction of the stapler with the Glissonian approach.…”
Section: Glissonian Versus Traditional Hilar Approachmentioning
confidence: 99%
“…8,14,15,[17][18][19][27][28][29] The remaining nine were comparative studies comparing CH to either EH and/or hemihepatectomy. 6,[11][12][13]16,22,25,30,31 Of these, one compared CH with hemihepatectomies, four compared CH to combined EH and hemihepatectomies and five evaluated CH versus EH. The five comparative studies comparing CH with EH included 432 patients who underwent CH and 598 who underwent EH (left/ right).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eight papers studied HCC patients only, all of which were from East Asia. 6,15,17,18,22,25,30,31 One study only specified the number of patients with primary or secondary liver tumours with no description of malignancy type. 27 The overall main indication was HCC comprising 85% (n = 1147) of patients, followed by CLM (n = 118 (8.8%)).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations